You can't catch me! - Hawes, Alison, 1952-; Roberts, David, 1970- (Barrington, IL : Rigby, 2002)
"Some boys on a playground take turns to be the 'running man,' the 'jumping man,' the 'hopping man,' and the 'skipping man'"--Back cover.
K-3.
K-3
Keywords: Play -- Juvenile fiction; School recess breaks -- Juvenile fiction; Play -- Fiction; Recess -- Fiction; Play -- Fiction; Recess -- Fiction; Readers (Publications)